Do Silêncio Ao Protagonismo: Por Uma Leitura Crítica Das Concepções De Infância E Criança - SIQUEIRA, Romilson Martins (2011)
This dissertation has researched about the conceptions of child and childhood in the field of Education and Psychology which have been produced by the groups registered in the CNPq Research Group Directory. This investigation has emerged the big tension of the theoretical fields which advocate the authority by defining child and childhood. The methodology was built on the bibliographical analyses comprising 151 works: 27 books, 70 book chapters and 54 academic papers. This quantitative enabled the theoretical production of 10 research groups on child and childhood in different regions of Brazil. This dissertation holds too as primary foundations the materialist and dialectal approach as well as the critical theory bedrocks within the scope of the Critical Social Psychology. The results have suggested that, since the second half of the 20th century, what have been construed as the history of Brazilian child and childhood and their conceptions have been highlighted and told predominantly thorough the juridical-legal apparatus. From the conception of minor to the conception of subject of right, the children were framed in the law s imperative. Likewise, a certain notion of a historical-cultural and a socially constructed childhood was widely propagated without considering the dialectal tension which touches themes such as class, natural and social development and childhood as a lifetime. Without this tension, it is likely that the conceptions will be instrumentalized as well as the child and childhood. Due to this process it was possible to apprehend: the absence of the theme of subjectivity; the presence of risks that involve reductionisms; the presence of highlighted identity by the Right; the presence of an epiphany of the child in the exacerbation of the child protoganism; the absence of the tension entrenched by the natural and biological as well as the social and the historical, and finally the absence of the debate on the child s development. Hence, it is argued in this dissertation that without the apprehension of what has been understood by child and childhood in the logical and historical field with no considerations to the objective and concrete conditions which produce the standards of sociability the child, the childhood and, consequently, the subjectivity remain abstract.